DRIVING FORCE OF ORGANIC FERTILIZER USE IN CENTRAL RIFT VALLEY OF ETHIOPIA: INDEPENDENT DOUBLE HURDLE APPROACH - Terefe, Aemro T.; Ahmed, Musa H. (Economics of Agriculture, 2016)
The objective of this study was to identify the important factors that influence both adoption and level of use of organic fertilizer among smallholder farmers in the Central Rift Valley of Ethiopia using a primary data collected from 161 sample respondents. An independent double hurdle model was used to address the objectives of the study on the assumption that adoption and level of organic fertilizer use by are two independent decisions influenced by different factors. Empirical estimates of the frst hurdle reveals that literacy status of the head, livestock holding, frequency of extension contact, distance to market and slope of the plot are statistically signifcant decision variables that affect the probability of adopting organic fertilizer. Meanwhile, estimates of the second hurdle revealed that, the extent of use of organic fertilizer was determined by livestock holding, access to credit distance to the market and slope of plot. This indicates that factors that affect adoption are not necessarily the same as those that influence intensity. Therefore, it is important to consider both stages in evaluating strategies aimed at promoting the adoption and use of organic fertilizer.